2022
DOI: 10.1001/jama.2021.23641
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Third Dose of BNT162b2 Vaccine With Incidence of SARS-CoV-2 Infection Among Health Care Workers in Israel

Abstract: IMPORTANCE Administration of a BNT162b2 booster dose (Pfizer-BioNTech) to fully vaccinated individuals aged 60 years and older was significantly associated with lower risk of SARS-CoV-2 infection and severe illness. Data are lacking on the effectiveness of booster doses for younger individuals and health care workers.OBJECTIVE To estimate the association of a BNT162b2 booster dose with SARS-CoV-2 infections among health care workers who were previously vaccinated with a 2-dose series of BNT162b2. DESIGN, SETTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 20 publications
5
76
1
2
Order By: Relevance
“…However, there is promising evidence that booster vaccines are effective in preventing infection from both Omicron and Delta variants [19]; moreover, the viral loads are lower (higher RT-PCR cycle thresholds) in post-booster cases than in cases with just two vaccinations [20]. Furthermore, some studies have already shown that rates of confirmed COVID-19 and severe illness were substantially lower among those who received a booster (third) dose of the BNT162b2 vaccine [10], and that booster vaccinations significantly reduced the incidence of SARS-CoV-2 infections (116 per 100,000 persondays prior to booster vaccination versus 12.8 per 100,000 after booster vaccination) for an estimated relative reduction of 93% (hazard ratio 0.07) [21]. Thus, the robust antibody response post-booster vaccination in our study supports the real-world benefit in blunting the pandemic's progress.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is promising evidence that booster vaccines are effective in preventing infection from both Omicron and Delta variants [19]; moreover, the viral loads are lower (higher RT-PCR cycle thresholds) in post-booster cases than in cases with just two vaccinations [20]. Furthermore, some studies have already shown that rates of confirmed COVID-19 and severe illness were substantially lower among those who received a booster (third) dose of the BNT162b2 vaccine [10], and that booster vaccinations significantly reduced the incidence of SARS-CoV-2 infections (116 per 100,000 persondays prior to booster vaccination versus 12.8 per 100,000 after booster vaccination) for an estimated relative reduction of 93% (hazard ratio 0.07) [21]. Thus, the robust antibody response post-booster vaccination in our study supports the real-world benefit in blunting the pandemic's progress.…”
Section: Discussionmentioning
confidence: 99%
“…Disease flares were based on patient report. Although administration of a third dose of SARS-CoV-2 vaccine has been associated with a significantly lower rate of COVID-19 infection in immunocompetent persons compared to two-dose vaccination, 9 , 10 associations between vaccine doses and antibody titres and clinical outcomes in immunosuppressed patients is required.…”
mentioning
confidence: 99%
“…In addition, protection induced by mRNA vaccines, one of the most widely distributed types of COVID-19 vaccines, wanes after a few months. Resistance to COVID-19 disease can be restored at least temporarily by a booster immunization but after a third dose of an RNA vaccine [31], protection declines after four months [32], and it is currently unknown if frequent boosts with such genetic vaccines within short intervals will continue to restore antibody titers. Long-lived plasma cells can maintain antibody responses often for years after vaccination or infection.…”
Section: Discussionmentioning
confidence: 99%